РОЛЬ МУГАМОВ В ВОСПИТАНИИ ПАТРИОТИЗМА У МОЛОДОГО ПОКОЛЕНИЯ. - Мамедова, Гасире Тофик кызы (Journal of Educational Sciences, 2016)
Автор мақалада жас ұрпақтың бойында патриоттық тəрбиені қалыптастырудағы Мугамов рөлі туралы сөз қозғайды. Көне тарихы бар музыка адамзат баласы еңбегінің нəтижесінде пайда болып, ұзақ жолдан өтті. Егер адам еңбектің жемісі болса, музыка – адамның рухани жан-дүниесін байытатын құрал екеніне тоқталады. The music having ancient history, has appeared thanks to the person and its work and has passed a long way of development. If the person - a work fruit music is means an inner world of the person. At all times music gave to people inspiration, their work, raised aspiration something to create. From time immemorial our forefathers went into battle with enemies under music sounds.